BIOCHEMICAL PARAMETERS OF THE EFFICIENCY OF AUTOPLASMA AND HYALURONIC ACID IN THE COMPLEX TREATMENT OF GENERALIZED PARODONTITIS - Vyshnevska, A.A.; Shnaider, S.A.; Reyzvikh, O.E.; Babenya, A.A.; Khrystova, M.T. (World of Medicine and Biology, 2020)
In this study, the dynamics of biomarkers of inflammation and the antioxidant system was assessed. The study involved 57 patients aged 36 to 55 years with a diagnosis of generalized parodontitis. In addition to basic therapy, the complex treatment of patients included regenerative techniques: injection of i-PRF, injection of plasmogel from platelet autoplasma and administration of hyaluronic acid. After the treatment, the most pronounced result of a decrease in the content of malondialdehyde was obtained in the group with a combination of plasmogel, hyaluronic acid and injectable platelet rich fibrin, after 1 year ‒ 0.18±0.01 mmol/L, after 2 years ‒ 0.21±02 mmol/l. In all groups, where the treatment with regenerative drugs was carried out, the activity of the catalase enzyme significantly increased in comparison with the comparison group, p2